Perancangan Layanan Informasi Museum La Galigo Dengan Pendekatan Virtual Tour - Ivan, Ivan (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2016)
La Galigo museum has a wide range of cultural and historical relics. Museum La Galigo established aimed as fostering the preservation of the cultural heritage of South Sulawesi. This study aims to create a virtual museum of La Galigo website so that people can recognize and know the information of the museum La Galigo especially the culture collections of the South Sulawesi. In addition to designing websites, a virtual tour concept is also applied as part of this study. Virtual tours are used to describe the atmosphere of the museum showroom. Virtual tour is applied using a 360 degree panoramic image and image mapping techniques. Virtual museum website designed attractive and easy to use